Polynomial-based mean weighted residuals methods for elliptic problems with nonlocal boundary conditions in the rectangle - Martín-Vaquero, Jesus (Nonlinear Analysis: Modelling and Control, 2014)
In this paper, polynomial-based mean weighted residuals methods for the solution of elliptic problems with nonlocal boundary conditions, in rectangular domains, are numerically studied. When these methods are employed, the nonclassical boundary conditions involve the solution of large systems of linear equations or least squares problems, hence some numerical techniques for these solvers are compared to show the importance of using efficient algorithms for this purpose. Different kinds of nodes are used to demonstrate how they can be employed to solve different numerical problems when large derivatives of the solution appear. We will also study how using extra precision and/or oversampling can often reduce the computational effort.These methods can also be combined with others (as, for example, finite difference or spline methods) to solve linear and nonlinear parabolic or hyperbolic partial differential equations. The numerical study of some techniques as those explained above can help to obtain significantly better numerical approximations with a smaller computational effort.
Keywords: elliptic PDEs; Galerkin methods; nonlocal conditions; pseudo-spectral methods